2011
DOI: 10.1007/s00702-010-0545-x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of acetylcholine on pain-related electric activities in the hippocampal CA3 of rats

Abstract: Acetylcholine (ACh) regulates pain perception in the central nervous system. However, the mechanism of action of ACh on pain-related neurons in the hippocampal CA3 is not clear. The present study aimed to determine the effect of ACh, muscarinic ACh receptors (mAChRs) agonist pilocarpine and mAChRs antagonist atropine on the pain-evoked responses of pain-excited neuron (PEN) and pain-inhibited neuron (PIN) in the hippocampal CA3 of normal rats. The trains of electric impulses applied to the sciatic nerve were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 40 publications
1
16
0
Order By: Relevance
“…The electric activities of PENs and PINs returned to normal level at 8 and 10 min after the noxious stimuli, respectively. Xiao et al [7], Yang et al [8], Li et al [9], and Jiao et al [32] focused on electric activities of pain-related neurons in the hippocampus after noxious stimuli for many years. In the hippocampal CA1 and CA3 area and dentate gyrus, cholinergic neurons and muscarinic receptors have effects on the electric activities of PENs and PINs, so that they are involved in pain modulation [79, 32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The electric activities of PENs and PINs returned to normal level at 8 and 10 min after the noxious stimuli, respectively. Xiao et al [7], Yang et al [8], Li et al [9], and Jiao et al [32] focused on electric activities of pain-related neurons in the hippocampus after noxious stimuli for many years. In the hippocampal CA1 and CA3 area and dentate gyrus, cholinergic neurons and muscarinic receptors have effects on the electric activities of PENs and PINs, so that they are involved in pain modulation [79, 32].…”
Section: Discussionmentioning
confidence: 99%
“…Neuropathic pain induced hippocampal interleukin-1 beta (IL-1 β ) mRNA levels upregulation, and the changes of IL-1 β mRNA expression correlated with the injured side of the hippocampus [6]. Xiao et al [7], Yang et al [8], and Li et al [9] reported in a series of studies that acetylcholine (ACh) influences the pain-induced discharge frequency and the electric activities of pain-related neurons in the hippocampus of rats.…”
Section: Introductionmentioning
confidence: 99%
“…At 20 min after injection, the electrical activities of all recorded pain-related neurons in the CPu reverted to the pretreatment values. We suggested that the recording duration of a pain-related neuron was 30 min to observe completely and eliminate the influence from repeated administrations [11,13,15]. The mammalian mAChR family contains five G protein-coupled receptors designated M1-M5.…”
Section: Discussionmentioning
confidence: 99%
“…The PENs, termed 'on-cells' by some researchers, may facilitate nociceptive transmission, whereas the PINs, termed 'offcells', probably inhibit nociception [14]. According to the distinctive responses of these neurons to nociceptive stimulus, their electrophysiological characteristics have been considered as important indices for nociceptive research [11,15]. An intra-CPu injection of 2 mg/2 ml norepinephrine increased the thermal pain threshold (long tail-flick latency) in rats and administration of 1 mg/2 ml phentolamine decreased this threshold (short tail-flick latency), suggesting that the CPu is involved in the nociceptive modulation [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation